ANALISIS KESALAHAN PENGGUNAAN POLA KALIMAT KATA PELENGKAP WAKTU PADA SISWA KELAS 8 SMPK IMMANUEL BILINGUAL CLASS PONTIANAK - Jufenna, Melissa; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTime complement is one of the types of quantity complement. It is one of the most important complement in Mandarin language. Time complement has an important role in daily conversation especially in expressing the duration of an activity. However, the complicated structure of time complement often causes students to have an error while constructing a sentence. The aim of this research is to observe the types of errors made by the eighth-grade students of SMPK Immanuel Bilingual Class Pontianak. The researcher used library research method and measuring method in this research. The test result has shown that there are 41.47% errors occurred in the first pattern of time complement sentence, 43.3% in the second pattern, 43.99% in the third pattern, and 45.69% in the fourth pattern. By using library research method, the researcher has found that the errors can be caused both by interlingual and intralingual interference. Keywords: Time Complement, Error Analysis, The Causes of Errors